2014
DOI: 10.5306/wjco.v5.i3.503
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine and breast cancer

Abstract: The thyroid hormones (THs), triiodothyronine (T3) and thyroxine (T4), are essential for survival; they are involved in the processes of development, growth, and metabolism. In addition to hyperthyroidism or hypothyroidism, THs are involved in other diseases. The role of THs in the development and differentiation of mammary epithelium is well established; however, their specific role in the pathogenesis of breast cancer (BC) is controversial. Steroid hormones affect many human cancers and the abnormal responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…3A and C). As THs influence the proliferation of breast cancer cells, it is worthwhile to consider that DIO3 expression in mammary neoplasias may play a role in modulating intracellular T 3 levels and thus contribute to tumor progression (De Sibio et al 2014). We observed moderate immunostaining of DIO3 in normal human mammary gland tissue and a significant expression of DIO3 staining in samples of invasive ductal carcinoma (I M Goemann, V Marczk, A L Maia, unpublished observations).…”
Section: Breast Cancer: Deiodinases As Markers or Effectors?mentioning
confidence: 61%
“…3A and C). As THs influence the proliferation of breast cancer cells, it is worthwhile to consider that DIO3 expression in mammary neoplasias may play a role in modulating intracellular T 3 levels and thus contribute to tumor progression (De Sibio et al 2014). We observed moderate immunostaining of DIO3 in normal human mammary gland tissue and a significant expression of DIO3 staining in samples of invasive ductal carcinoma (I M Goemann, V Marczk, A L Maia, unpublished observations).…”
Section: Breast Cancer: Deiodinases As Markers or Effectors?mentioning
confidence: 61%
“…In breast cancer cell lines it has been demonstrated that tri-iodothyronine can augment the cell proliferation potential of estrogens, thus possibly increasing the malignant potential in breast cancer cells lines. 31,32 This is supported by a recent trial where higher endogenous serum tri-iodothyronine was associated with breast tumours demonstrating more aggressive characteristics 33 and increased mortality. 34 However, the association with breast cancer was of borderline statistical significance in the overall group and the association was not related to the number Wald test for significance of the variable taken as a whole, v 2 (4) = 33Á64, P < 0Á001.…”
Section: Discussionmentioning
confidence: 80%
“…The possible association with breast cancer is a concern. In breast cancer cell lines it has been demonstrated that tri‐iodothyronine can augment the cell proliferation potential of estrogens, thus possibly increasing the malignant potential in breast cancer cells lines . This is supported by a recent trial where higher endogenous serum tri‐iodothyronine was associated with breast tumours demonstrating more aggressive characteristics and increased mortality .…”
Section: Discussionmentioning
confidence: 84%
“…If this is the case, then among the subgroup of breast cancer patients expressing THRa1, it may be hypothesized that outcomes might be improved by (a) lowering the systemic levels of thyroid hormone [26][27][28], (b) inhibiting THRa1, or (c) up-regulating THRa2 [29,30]. The possibility of lowering the systemic levels of thyroid hormone using commercially available drugs is intriguing, but further study of this potential therapy is limited by conflicting results regarding the effect of hypothyroidism in women with breast cancer [26][27][28][31][32][33][34][35][36][37][38]. It is possible that the thyroid receptor expression in a breast tumour affects its response to thyroid hormone and that those expressing an ''unfavourable'' thyroid receptor profile may benefit from a reduction in thyroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%